KEADILAN SOSIAL DALAM PENARIKAN PAJAK PROGRESIF: ANALISIS DAMPAK SISTEM PAJAK TERHADAP BEBAN PAJAK PADA WARGA KAYA DAN MISKIN DI INDONESIA - Yunita Rodho Rahmawati (Pusat Penerbitan dan Publikasi Ilmiah FEB-UMI, 2024)
Progressive tax collection, which aims to share the tax burden evenly between rich and poor, is an important tool for realizing social justice in Indonesia. This research examines the impact of a progressive tax system on social welfare and income distribution, especially for rich and poor citizens. This research uses qualitative and quantitative analysis approaches to evaluate how higher tax rates imposed on higher incomes can reduce social inequality and strengthen social programs. The research results show that although progressive taxes can reduce social inequality, progressive taxes cannot actually reduce social inequality. Therefore, this research suggests progressive tax management reforms that prioritize transparency, equality, and more efficient budget allocation for sustainable social programs.